Analisis Dampak Pembangunan Kelas Kontainer terhadap Citra Institusi Universitas Singaperbangsa Karawang - Utami, Sri Setiawati; Zahra, Vanissa Fatimatul; Tursina, Zenit; Desviana, Alyssa; Manda, Gusganda Suria; Fauziyah, Syifa (Jurnal Bisnis, Manajemen, dan Ekonomi, 2025)
Public attention and responses have emerged due to the placement of container classrooms at Singaperbangsa Karawang University (UNSIKA), particularly regarding the level of comfort and quality of educational facilities provided. Students, lecturers, and the general public have varying perspectives regarding the Rp6.4 billion fund, which has the potential to damage the institution's reputation. This study aims to analyze how stakeholders' views on UNSIKA's image are affected by the placement of container classrooms. The method employed is quantitative, conducted through a survey by distributing questionnaires to 204 respondents from the academic community and the general public. Data analysis was carried out using descriptive statistics, Pearson correlation testing, and simple linear regression. The findings indicate a significant and positive relationship between the construction of container classrooms and the institution's image, with a correlation coefficient value of 0.763 and a significance level of 0.000 (<0.05). The regression equation Y = 7.316 + 0.814X indicates that perceptions of the construction of container classrooms make a significant contribution to improving the institution's image. The R-squared value of 0.581 indicates that 58.1% of the changes in the image of the institution can be explained by the variable of constructing container classrooms. This study concludes that the construction of container classes has a significant impact on the formation of institutional image and can be a positive strategy if balanced with improving the quality and public communication.